The Dark Hills divide - Carman, Patrick (New York : Orchard Books, 2005)
Inquisitive twelve-year-old Alexa Daley is spending another summer in the walled town of Bridewell. This year, she is set on solving the mystery of what lies beyond the walls. Legend says the walls were built to keep out an unnamed evil that lurks in the forests and The Dark Hills. But what exactly is it that the townspeople are so afraid of? As Alexa begins to unravel the truth, pushing beyond the protective barrier she's lived behind all her life, she discovers a strange and ancient enchantment -- and exposes a danger that could destroy everything she holds dear.
Keywords: Daley, Alexa (Fictitious character) -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Forest animals -- Juvenile fiction; Forests and forestry -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction